Respuesta :

Answer = refer to the pictures

hope this helps :)

Ver imagen synicalcuh
Ver imagen synicalcuh
Ver imagen synicalcuh
Ver imagen synicalcuh
Hi1315

Answer:

First of all you have to know that,

( + ) × ( + ) = ( + )

( - ) × ( - ) = ( + )

( + ) × ( - ) = ( - )

Now let us solve now.

#1

- ( 5x + 3y + 5z ) + 6x

- 5x - 3y - 5z + 6x

- 5x + 6x - 3y - 5z

x - 3y - 5z

#2

- ( 4x - 5y + 8 )

- 4x +5y - 8

#3

6t - ( 5r - 4p + 9 )

6t - 5r + 4p -9

#4

-2 ( 3x + 7y )

- 6x - 14y

Hope this helps you :-)

Let me know if you have any other questions :-)